Industrial excess heat for district heating in Denmark. (1st November 2017) - Bühler, Fabian; Petrović, Stefan; Karlsson, Kenneth; Elmegaard, Brian
Highlights: Method for utilisation potential of industrial excess heat for district heating. Industrial excess heat from thermal processes is quantified at single production units. Linking of industrial excess heat sources and district heating demands done in GIS. Excess heat recovery using direct heat transfer and heat pumps. 5.1% of the Danish district heating demand could be supplied by industrial excess heat. Abstract: Excess heat is available from various sources and its utilisation could reduce the primary energy use. The accessibility of this heat is however dependent amongst others on the source and sink temperature, amount and potential users in its vicinity. In this work a new method is developed which analyses excess heat sources from the industrial sector and how they could be used for district heating. This method first allocates excess heat to single production units by introducing and validating a new approach. Spatial analysis of the heat sources and consumers are then performed to evaluate the potential for using them for district heating. In this way the theoretical potential of using the excess heat for covering the heating demand of buildings is determined. Through the use of industry specific temperature profiles the heat usable directly or via heat pumps is further found. A sensitivity analysis investigates the impact of future energy efficiency measures in the industry, buildings and the district heating grid on the national potential. The results show that for the case study of Denmark, 1.36 TWh of district heat could be provided annually with industrial excess heat from thermal processes which equals 5.1% of the current demand. More than half of this heat was found to be usable directly, without the need for a heat pump.